2016
DOI: 10.1002/polb.24142
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of monodisperse/bidisperse polymer melt crystallization

Abstract: We use large scale coarse‐grained molecular dynamics simulations to study the kinetics of polymer melt crystallization. For monodisperse polymer melts of several chain lengths under various cooling protocols, we show that short chains have a higher terminal crystallinity value compared to longer ones. They align at the early stages and then cease evolving. Long chains, however, align, fold into lamella structures and then slowly optimize their dangling ends for the remaining simulation time. We then identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…The overall crystallinity of B166, close to that of unimodal system U166, is a compromise between that of the short and long chains. Triandafilidi et al 34 have also reported a similar conclusion in the crystallization competition of the two components. In Figure 2c, we have plotted the ratio of final long-chain crystallinity divided by short-chain crystallinity at various temperatures.…”
Section: Isothermal Crystallizationmentioning
confidence: 58%
“…The overall crystallinity of B166, close to that of unimodal system U166, is a compromise between that of the short and long chains. Triandafilidi et al 34 have also reported a similar conclusion in the crystallization competition of the two components. In Figure 2c, we have plotted the ratio of final long-chain crystallinity divided by short-chain crystallinity at various temperatures.…”
Section: Isothermal Crystallizationmentioning
confidence: 58%
“…We determine the average length of crystalline sequences L c (stem length) from the size distribution of ordered segments along the chains. [19]. The average length of crystalline sequences is almost constant, i.e., L c ≈ 10 independent of N and T. As demonstrated in the inset of Fig.…”
mentioning
confidence: 68%
“…Recently, a large amount of work dedicated to crystallization of simple polymers, including models for polyethylene and poly(vinyl alcohol), has been reported using molecular dynamics. [14][15][16][17][18][19][20][21][22][23][24][25] These studies cover the investigation of molecular mechanisms of crystal growth, [17][18][19] effects of polymer chain length, 24 and chain stiffness. 25 Possible crystallization mechanisms can be different in different polymers, although some common features can be present.…”
mentioning
confidence: 99%